2003
DOI: 10.1144/gsl.sp.2003.214.01.10
|View full text |Cite
|
Sign up to set email alerts
|

A review of the occurrence and origin of abiogenic hydrocarbons in igneous rocks

Abstract: Reports on the presence of hydrocarbons in igneous rocks have been on the increase and generating greater interest in the scientific community over the last 20 years. Most of the occurrences are due to the incorporation of organic material into the magmatic systems. However, reports on the presence of hydrocarbons formed by abiogenic processes have also increased in recent years, suggesting that these hydrocarbons may not be as rare as previously thought and may have implications for natural gas resources in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 57 publications
0
49
0
Order By: Relevance
“…The presence of magnetite in massive sulfides from the footwall ore zones suggests that the sulfide liquids crystallized along a magnetite-saturated liquidus; therefore, the ambient fO 2 conditions in the vicinity of the crystallizing sulfides could not have been as reducing as QFM-4. At such temperature and moderate fO 2 , the dominant C-O-H species in the inclusions should be CO 2 (Salvi and Williams-Jones 1997;Potter and Konnerup-Madsen 2003). Additionally, the higher hydrocarbons in the S CH4 inclusions would be expected to convert completely to graphite above 500°C in contact with a halide-melt phase (Shock 1990).…”
Section: Origin Of the Brine-ch 4 Assemblagementioning
confidence: 99%
“…The presence of magnetite in massive sulfides from the footwall ore zones suggests that the sulfide liquids crystallized along a magnetite-saturated liquidus; therefore, the ambient fO 2 conditions in the vicinity of the crystallizing sulfides could not have been as reducing as QFM-4. At such temperature and moderate fO 2 , the dominant C-O-H species in the inclusions should be CO 2 (Salvi and Williams-Jones 1997;Potter and Konnerup-Madsen 2003). Additionally, the higher hydrocarbons in the S CH4 inclusions would be expected to convert completely to graphite above 500°C in contact with a halide-melt phase (Shock 1990).…”
Section: Origin Of the Brine-ch 4 Assemblagementioning
confidence: 99%
“…For example, numerous studies have demonstrated that sill intrusions may (1) locally heat and mature organic matter within the host rock, generating oil and/or gas (e.g., Rodriguez Monreal et al, 2009), (2) be associated with 1 overlying dome structures that can be described as four-way dip closures Jackson et al, 2013;Magee et al, 2014Magee et al, , 2015, and (3) promote the development of local intense fracture networks that locally increase host rock permeability (Witte et al, 2012;Agirrezabala, 2015;Senger et al, 2015). A robust understanding of the mechanics of magma emplacement in volcanic basins is therefore required to derisk hydrocarbon exploration in volcanic basins (Potter and Konnerup-Madsen, 2003;Schutter, 2003aSchutter, , 2003b.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many studies, there was and is considerable debate whether such fluids are of a magmatic origin and represent primary high-temperature conditions (mantle gas theory) or are the result of various secondary processes (e.g., Konnerup-Madsen 2001;Potter and Konnerup-Madsen 2003;Krumrei et al 2007;Beeskow et al 2006;Nivin et al 1995Nivin et al , 2001Nivin et al , 2005Potter et al 1998Potter et al , 2004Potter and Longstaffe 2007), but scientists agreed on the abiogenic origin of the methane-rich fluids found in the Ilímaussaq rocks and in similar agpaitic complexes in Russia (see above). This was, however, largely questioned by Laier and Nytoft (2012) who argued that the hydrocarbons of Ilímaussaq are of biogenic origin and migrated to Ilímaussaq from deep oil seeps offshore west of Greenland during the Cretaceous.…”
Section: Fluid Evolutionmentioning
confidence: 99%